(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the utilization of and satisfaction with social work (SW) services among inpatients at Tien Giang Psychiatric Hospital in 2026. Subjects and methods: A cross-sectional study was conducted on 272 participants who were family members of inpatients aged 18 years or older and capable of communication at Tien Giang Psychiatric Hospital. Data were collected using a structured questionnaire. Data were analyzed using SPSS version 20.0. Results: The utilization rate of counseling services was high (70-83%), whereas it was notably lower for emergency support services (20.6%). The proportion of participants satisfied with specific services was 78.6% for counseling, 36% for resource linkage, and 27.5% for communication. Conclusion: While social work activities have been implemented, their delivery remains fragmented, particularly regarding communication networks and resource linkage.